2011
DOI: 10.3390/su3071064
|View full text |Cite
|
Sign up to set email alerts
|

Public-Private Partnerships and Sustainable Agricultural Development

Abstract: Agriculture in Africa is not sustainable because average yields have been stagnating for decades due to underinvestment, especially in the development of agricultural markets, crop improvement and the sustainable management of agricultural systems. Low public sector funding for agricultural research and lack of incentives for the private sector to operate in areas where there is no market largely explain the yield gap in many food-importing developing countries. Yet, there are effective ways in which the publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 3 publications
0
34
0
Order By: Relevance
“…Nowadays, public-private partnership (PPP) is considered as an effective system to bring together the public and the private sectors towards enhancing agricultural sustainability in the developing world. Ferroni and Castle [241] presented several promising PPPs in which the Syngenta Foundation for Sustainable Agriculture has been actively involved over the last decade. These partnership projects in Africa include a lodging tolerant and semi-dwarf tef [242], rust-resistant wheat, and biofortification of sweet potato.…”
Section: Establish Partnership With Relevant Stakeholdersmentioning
confidence: 99%
“…Nowadays, public-private partnership (PPP) is considered as an effective system to bring together the public and the private sectors towards enhancing agricultural sustainability in the developing world. Ferroni and Castle [241] presented several promising PPPs in which the Syngenta Foundation for Sustainable Agriculture has been actively involved over the last decade. These partnership projects in Africa include a lodging tolerant and semi-dwarf tef [242], rust-resistant wheat, and biofortification of sweet potato.…”
Section: Establish Partnership With Relevant Stakeholdersmentioning
confidence: 99%
“…According to Ferroni and Castle (2011), small farmers in developing countries generally have limited access to technology, extension services, and market integration. This condition also occurs in a small Mangosteen farmers in Banyuwangi District that cannot meet the demands of export markets such as the continuity of quantity, quality, food safety and competitive prices.…”
Section: Discussionmentioning
confidence: 99%
“…It was therefore not surprising to find the eight constructs in an empirical study on a Dutch cable company reduced to a smaller number of five factors: openness (containing items of the original concepts of coordination, communication, dependence, and trust); mutual interest in the partnership (related to trust and conflict); equality (derived from items on dependence and communication); conflict management (related to conflict and diversity); and closeness. In the same vein, it is interesting to note that strands of literature on partnerships, that differ in the scope and complexity of the partnerships examined, converge on similar determinants of success: mutual interest in the partnership=involvement (Ferroni & Castle 2011;de Waal, 2012); trust among the stakeholders (Drost et al, 2012) as indicated by mutual interest and openness in the partnership ; and the relational aspects of partnerships (Scott, 2011).…”
Section: Literature Reviewmentioning
confidence: 95%